1991
DOI: 10.1177/002076409103700308
|View full text |Cite
|
Sign up to set email alerts
|

Experienced Turkish Nurses' Attitudes towards Mental Illness and the Predictor Variables of their Attitudes

Abstract: General attitudes towards mental illness, attitudes towards two vignettes, and possible predictor variables of these attitudes were investigated among experienced Turkish nurses. The analyses showed that the nurses accepted both organic and psychological causation and had rather positive views on drug treatment, psychotherapy, and prognosis. However, they were more favourably disposed towards psychological causation and psychotherapy; the paranoid schizophrenia description was more readily perceived as mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
(28 reference statements)
0
6
0
1
Order By: Relevance
“…Three studies used the Attitudes Toward Acute Mental Illness Scale (ATAMH33) (Baker, Richards, & Campbell, 2005) and four studies used Community Attitudes towards Mental Illness (CAMI) (Taylor, Dear, & Hall, 1979; Taylor & Dear, 1981). The following measures were in at least one study: The Level of Contact Report (Holmes, Corrigan, Williams, & Canar, 1999), the Opinion about Mental Illness (Madianos, Madianou, Vlachonikolis, & Stefanis, 1987), the Authoritarianism Scale (Adorno, 1950), Social Distance (Arkar, 1991), Burden of Illness (Eker & Arkar, 1991), Jefferson Scale of Empathy-Health Profession version (Hojat, Gonnella, Nasca, Mangione, & et al, 2002), Attitudes of Mental Illness Questionnaire (Luty, Fekadu, Umoh, & Gallagher, 2006), Social Interaction Scale (Kelly, St Lawrence, Smith, & Hood, 1987), Social Acceptance Scale (Angermeyer & Matschinger, 1997), and Standardized Stigma Questionnaire (Haghighat, 2005). Kukulu and Ergun, (2007) utilized an adaptation of multiple instruments, but the researchers were unable to assess its validity because the instruments’ descriptions and psychometric testing were only being available in studies published in the Turkish language.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used the Attitudes Toward Acute Mental Illness Scale (ATAMH33) (Baker, Richards, & Campbell, 2005) and four studies used Community Attitudes towards Mental Illness (CAMI) (Taylor, Dear, & Hall, 1979; Taylor & Dear, 1981). The following measures were in at least one study: The Level of Contact Report (Holmes, Corrigan, Williams, & Canar, 1999), the Opinion about Mental Illness (Madianos, Madianou, Vlachonikolis, & Stefanis, 1987), the Authoritarianism Scale (Adorno, 1950), Social Distance (Arkar, 1991), Burden of Illness (Eker & Arkar, 1991), Jefferson Scale of Empathy-Health Profession version (Hojat, Gonnella, Nasca, Mangione, & et al, 2002), Attitudes of Mental Illness Questionnaire (Luty, Fekadu, Umoh, & Gallagher, 2006), Social Interaction Scale (Kelly, St Lawrence, Smith, & Hood, 1987), Social Acceptance Scale (Angermeyer & Matschinger, 1997), and Standardized Stigma Questionnaire (Haghighat, 2005). Kukulu and Ergun, (2007) utilized an adaptation of multiple instruments, but the researchers were unable to assess its validity because the instruments’ descriptions and psychometric testing were only being available in studies published in the Turkish language.…”
Section: Resultsmentioning
confidence: 99%
“…They prefer social distance from people with schizophrenia. In Turkish studies, it is reported that the public have negative attitudes towards patients with schizophrenia and that they dominantly show a tendency to reject them, and also that they hesitate to become socially close to these patients (18,21–23). In Taskin's study (Taskin et al 2003), the public in rural areas sufficiently recognise schizophrenia but have a tendency to stigmatise schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first theme was the health care providers' negative attitudes toward individuals with schizophrenia (AYDIN et al 2003;EKER & ARKAR 1991;KUKULU & ERGUN 2007;OZYIGIT et al 2004;SAVAS et al 2002;UCOK et al 2004). Three subthemes were identified under this category.…”
Section: Health Care Providers' Negative Attitudes Toward Schizophreniamentioning
confidence: 99%